AB0266 ANALYSIS OF STRESS AND FATIGUE IN PATIENTS WITH RHEUMATOID ARTHRITIS USING A DIGITIZING DEVICE. (2nd June 2020) - Tada, M.; Yamada, Y.; Mandai, K.; Hidaka, N.
Abstract : Background: Stress and fatigue are evaluated subjectively by patients using a visual analog scale (VAS) and questionnaires such as the SF-36 and the FACIT Fatigue Scale. Such evaluations are based on patients' self-reported outcomes. It is difficult to evaluate stress and fatigue objectively. A digitizing device was used to quantify stress objectively. Objectives: To evaluate the correlations of a digitizing device and a VAS or a questionnaire about stress and fatigue, and the relationships with disease activity of patients with rheumatoid arthritis (RA). Methods: Data from a prospective observational study (CHIKARA study: Correlation researcH of sarcopenIa, sKeletal muscle and disease Activity in Rheumatoid Arthritis) were used. The study protocol was reported previously 1 . A total of 84 RA patients entered the study and were evaluated using a stress digitizing device (Smart Pulse, MEDICORE Co. LTD). This device evaluates stress based on heart rate variability theory 2 . The objective physical stress score (O-physical ST), mental stress score (O-mental ST), and total stress score (O-total ST) were calculated, ranging from 0 to 100 (higher score indicating greater stress). A questionnaire for stress, the Perceived Stress Scale 3 (PSS) 10 Japanese version (minimum 0, maximum 40), and VAS evaluations of stress (stress-VAS) and fatigue (fatigue-VAS) were carried out. The correlations between subjective and objective methods were analyzed. The relationships between stress, fatigue, and disease activity of RA patients were examined. Results: The patients' mean age was 68.6 years (women n=66, men n=18), disease duration was 8.8 years, DAS28ESR was 3.24, and modified Health Assessment Questionnaire (mHAQ) was 0.5. The average PSS10 was 26.1, which was higher than in healthy individuals (20.3). The fatigue-VAS was higher than the stress-VAS (41.3 vs 34.5 mm). The O-physical ST score was similar to the O-mental ST score (39.5 vs 37.4). Correlations are shown in Table. The O-physical ST was positively correlated with the fatigue-VAS (R=0.243 p=0.026), and the O-mental ST was also positively correlated with the stress-VAS (R=0.267 p=0.014). However, there was no correlation between the PSS10 and objective stress parameters. The DAS28-ESR was correlated with the fatigue-VAS (R=0.223 p=0.041) and the O-total ST (R=0.329 p=0.002). The stress scale (O-total ST) was worse with moderate and high disease activity than in remission (Figure). Conclusion: The stress score obtained by an objective digitizing device was correlated with stress- and fatigue-VAS scores. However, there was no correlation with the PSS10 questionnaire. It was found that the fatigue-VAS score and the objective total stress score were high with worse disease control. References: [1]Tada, M., Yamada, Y., Mandai, K. & Hidaka, N. Matrix metalloprotease 3 is associated with sarcopenia in rheumatoid arthritis - results from the CHIKARA study. Int J Rheum Dis 21, 1962-1969, doi:10.1111/1756-185X.13335 (2018). [2]Heart rate variability: standards of measurement, physiological interpretation and clinical use. Task Force of the European Society of Cardiology and the North American Society of Pacing and Electrophysiology. Circulation 93, 1043-1065 (1996). [3]Cohen, S., Kamarck, T. & Mermelstein, R. A global measure of perceived stress. J Health Soc Behav 24, 385-396 (1983). Disclosure of Interests: None declared